2017
DOI: 10.1016/j.jaac.2017.05.005
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Gaze Differences to Social and Nonsocial Information Between Individuals With and Without Autism

Abstract: Objective Numerous studies have identified abnormal gaze in individuals with autism. Yet only a limited number of findings have been replicated, the magnitude of effects is unclear, and the pattern of gaze differences across stimuli remains poorly understood. To address these gaps, we conducted a comprehensive meta-analysis of autism eye tracking studies. Method PubMed and manual search of 1,132 publications were used to identify studies comparing looking behavior to social and/or nonsocial stimuli between i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
227
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 257 publications
(252 citation statements)
references
References 33 publications
21
227
1
3
Order By: Relevance
“…This lead to a smaller, unbalanced, and less well characterized TD group; for example, this group was assumed to have an IQ within the normal range, and although sex was balanced across the group as a whole, the older TD group included significantly more females ( χ 2 (1) = 5.3221, P = 0.02). Frazier et al () did not find that IQ or sex differences were a mediating factor in determination of effect sizes in social attention in ASD. However, it is important to be aware of these limitations.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This lead to a smaller, unbalanced, and less well characterized TD group; for example, this group was assumed to have an IQ within the normal range, and although sex was balanced across the group as a whole, the older TD group included significantly more females ( χ 2 (1) = 5.3221, P = 0.02). Frazier et al () did not find that IQ or sex differences were a mediating factor in determination of effect sizes in social attention in ASD. However, it is important to be aware of these limitations.…”
Section: Discussionmentioning
confidence: 94%
“…There is evidence that differences in visual attention emerge as early as within the first year in ASD (Ozonoff et al, ; Sasson & Elison, ; Chawarska, Macari, & Shic, ; Jones & Klin, ; Shic, Macari, & Chawarska, ), and a small study of children aged 2–5 years ( n = 10 ASD, 14 TD) using VET indicated reduced or atypical object exploration in the ASD group compared to a TD (Sasson, Elison, Turner‐Brown, Dichter, & Bodfish, ), which increases with age for both groups (Elison et al, 2012). Frazier et al's () review did not find that gaze deficits in attention to social stimuli were moderated by age, sex, or cognition. However, some observations appear to not hold stable across age in ASD (Guillon, Hadjikhani, Baduel, & Roge, ).…”
Section: Introductionmentioning
confidence: 95%
“…Although visual orienting is directly observable, it may index a more basic neuropsychological process than other behavioral symptoms and can be objectively measured using eye tracking. A review of 122 studies indicated atypical gaze patterns across the lifespan in people with ASD, consistent with fundamental deficits in selecting and attending to information needed to perceive social interactions accurately 88. Numerous studies have examined early correlates of these findings in high risk infants 89909192939495969798.…”
Section: Potential For Presymptomatic Detection: Advances In Biomarkementioning
confidence: 99%
“…For example, in the social domain, both adults and children with autism spectrum disorder (ASD) spend less time looking at eye and face regions, and more time looking at non-social stimuli than healthy controls (HCs) (Frazier et al, 2017). For example, in the social domain, both adults and children with autism spectrum disorder (ASD) spend less time looking at eye and face regions, and more time looking at non-social stimuli than healthy controls (HCs) (Frazier et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Eye-tracking research can provide insights into cognitive, social, and emotional processes in psychiatric disorders. For example, in the social domain, both adults and children with autism spectrum disorder (ASD) spend less time looking at eye and face regions, and more time looking at non-social stimuli than healthy controls (HCs) (Frazier et al, 2017). These differences are associated with impairments in areas of social cognition, for example, less time spent looking at the eyes predicts impairments in recognizing fearful expressions in adults with Asperger's syndrome (Corden, Chilvers, & Skuse, 2008).…”
Section: Introductionmentioning
confidence: 99%